PENCEDERAAN KEPERCAYAAN PADA RELASI PERSAHABATAN REMAJA - , Dede Fitriana A ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The experience in a friendship was not always a positive one. Trust as the foundation in a friendship might be violated. Trust was considered to be violated when the trustor (the one who the people trust) had a perception that the trustee (the one who was trusted) did not behave according to the expectation of the general norms (Roth & Sitkin, 1993). The research was to find the general description and the psychological dynamic within the trust violation in a adolescentâs friendship. A friendship as a form of interpersonal relationship implemented the theory of interdependence. The research was performed in two phases namely the quantitative one in the form of a survey toward 117 students of the Faculty of Psychology, Gadjah Mada University, and the qualitative one in the form of an interview to 4 respondents. The results of the research showed that the forms of trust violation were the behavior and the personal quality. The trust violation included exposure of a secret, avoidance of fulfilling a promise, lie, verbal attack, communication and interest. In addition to the violation, the research also uncovered the reasons of intimacy, emotion after being violated, the magnitude of violation, the consideration of the magnitude, the comparison of intimacy before and after the violation and the response of being violated. Then, the dynamic of the violation explained multiple variations of a friendship after being violated.